Seismic response of adjacent coupled buildings with MDOF systems using SAVD device - Tande, S. N.; Shinde, D. N. (Journal of Structural Engineering, 2024)
Coupled building control is shown to be a viable method to protect tall buildings from seismic excitation. The philosophy is to allow structures, vibrating at different frequencies, to exert control forces upon one another. Also, the possibility of ‘pounding’ of buildings is reduced. This paper proposes a new semi-active device, composed of two fixed orifice viscous fluid dampers installed in the form of ‘V’ whose top ends are attached to the upper floor and their lower ends to a point that can move along a vertical rod. The mechanism is termed the Semi-Active-Variable-Damping (SAVD) device. By varying its position, one can provide optimal instantaneous damping to the structure to minimize its seismic response. To determine the proper position of the moving end of the device, two algorithms based on a variation of the Instantaneous Optimal control theory were developed. The modified algorithms, referred to as ‘Qv’, are used to compute the response of coupled structures with multi degree of freedom systems. The responses of the structural systems with the semi-active variable damping (SAVD) device subjected to different earthquakes are numerically studied and compared with those obtained with fixed dampers.